Identification of Babesia Infection in Dogs with Tick Infestation in Chennai, Tamil Nadu: A Molecular Diagnostic Approach - Vidhya, Munagala Sree; Arunkumar, Selvarayar; Palavesam , Azhahianambi; Chandrasekar, Munisamy; Kumar, Tuticorin Maragatham Alagesan Senthil (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Canine babesiosis, a tick-borne disease caused by protozoa of the genus Babesia, is a significant concern in tropical regions like India, where the warm, humid climate facilitates tick proliferation. This study was aimed to determine the prevalence of Babesia infection in dogs with tick infestation in Chennai, Tamil Nadu, using a molecular diagnostic approach. Blood and tick samples were collected from 158 dogs exhibiting clinical signs suggestive of haemoprotozoan infection. Following DNA extraction, PCR targeting the 18S rRNA gene of Babesia spp. was performed. Tick species identification was based on morphological characteristics and PCR amplification of the 12S rDNA gene of Rhipicephalus sanguineus s.l. Out of the 158 samples, 29 (18.35%) were positive for Babesia infection, with Rhipicephalus sanguineus s.l. identified as the predominant tick vector. These findings highlight the substantial prevalence of canine babesiosis in Chennai and emphasize the need for enhanced surveillance and preventive measures to control tick populations and safeguard canine health. Molecular diagnostic tools like PCR are essential for accurate and early diagnosis of this potentially fatal disease.